Soil Liquefaction Problems in the Foundations Hydraulic Structures - K. P. Morgunov; M. A. Kolosov (Наука и техника)
An analysis of the probability and conditions for the occurrence of soil liquefaction at the base and in the vicinity of hydraulic structures is presented in the paper. As a rule, hydraulic structures are erected in the valleys of watercourses, the structure of the soil in which contributes to the occurrence of liquefaction processes. These soils are fine-grained, non-cohesive, usually consisting of fine- and medium-grained or silty sands, sandy loams, interspersed with layers of loams. Massifs under pressure hydraulic structures are quite water-saturated. Soil liquefaction occurs as a result of the destruction of structural bonds between particles in water-saturated dispersed soils under the action of stresses of various types. An external dynamic or static load applied to a water-saturated massif composed of weak, finely dispersed soils can lead to a complete or partial loss of soil bearing capacity and its transition to a fluid state. The magnitude of soil resistance to shear is determined by the degree of its water saturation; at a moisture content of about 20 %, the angle of repose of sandy soils is significantly reduced. The restoration of the strength properties of soils is prevented by the pore water pressure, the process of compaction (consolidation) of the soil mass occurs after the water is squeezed out of the pores, the flow time of which depends on the filtration properties of the massif. Liquefaction of soils leads to a disruption in the normal functioning of a hydraulic structure, the creation of emergency situations. The paper provides examples of accidents at hydraulic structures in Russia caused by liquefaction phenomena. It is noted that the main directions of protecting the structures of hydraulic structures from dangerous liquefaction are to prevent the possibility of liquefaction and the reduction of its harmful effects.  In this regard, several methods are considered – compaction and strengthening of soils at the base of structures; filtering surcharge device using geotextiles and geogrids; creation of an effective drainage system.